Identifikasi Faktor Penyebab Ineffective Change Dalam Resistensi Perubahan Budaya Organisasi - Tamyizul Ibad (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2022)
Education is something that is very important for human life. By having an education, life is more secure. Education is the key for a nation to prepare a better future, so that it is able to compete with other nations. As a dynamic system, education is constantly highlighted by the community, government and stake holders accompanied by the emergence of increasingly complex educational problems. Changes in organizational culture on the one hand can improve performance, but on the other hand, they can also experience failures if they are not properly prepared and managed. Resistance to changes in organizational culture is essentially some individual and some organizational. Resistance to change of any nature remains a significant effect on changes in the existing organizational culture. The significance of the influence of changes in organizational culture will give rise to failures or ineffectiveness of the changes made. A leader should be able to make changes and overcome resistance to change. Without the changes made, an organization will not be able to develop properly. With the change in organizational culture towards a better one, the process of change is said to be effective.